2021
DOI: 10.3389/fimmu.2021.687102
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of MHC Class I Region-Encoded E3 Ubiquitin Ligases in Innate Immunity

Abstract: The major histocompatibility complex (MHC) class I (MHC-I) region contains a multitude of genes relevant to immune response. Multiple E3 ubiquitin ligase genes, including tripartite motif 10 (TRIM10), TRIM15, TRIM26, TRIM27, TRIM31, TRIM38, TRIM39, TRIM40, and RING finger protein 39 (RNF39), are organized in a tight cluster, and an additional two TRIM genes (namely TRIM38 and TRIM27) telomeric of the cluster within the MHC-I region. The E3 ubiquitin ligases encoded by these genes possess important roles in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 84 publications
(101 reference statements)
0
20
0
Order By: Relevance
“…In addition, these TRIMs-B30.2 evolve significantly faster than other TRIMs based on the calculated ratio of the non-synonymous substitution rate ( Ka ) to the synonymous substitution rate ( Ks ) [ 4 ]. Recently, several studies have identified a cluster of TRIM-B30.2 genes flanking the human major histocompatibility complex (MHC) gene locus, a well-known immune gene [ 18 ]. Functional experiments have also demonstrated that TRIMs-B30.2 tend to be involved in host immune defense against viral infections in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these TRIMs-B30.2 evolve significantly faster than other TRIMs based on the calculated ratio of the non-synonymous substitution rate ( Ka ) to the synonymous substitution rate ( Ks ) [ 4 ]. Recently, several studies have identified a cluster of TRIM-B30.2 genes flanking the human major histocompatibility complex (MHC) gene locus, a well-known immune gene [ 18 ]. Functional experiments have also demonstrated that TRIMs-B30.2 tend to be involved in host immune defense against viral infections in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…While no obvious functional associations were identified in gene set enrichment analysis of the significant DMPs and DMRs from our regression analysis, the within-pair analysis identified enrichment in immune-related terms. The top DMR identified in this study is located in the gene body of TRIM39-RPP21 , a read-through transcript enjoining the N-terminus RING finger and B-box domains of TRIM39 and RPP21 and located within the major histocompatibility complex class I region of chromosome 6 22 , 23 . The nine associated probes in this region are hypomethylated in cases compared to controls.…”
Section: Discussionmentioning
confidence: 90%
“…Membrane-anchored E3 ligases of the Modulator of Immune Recognition (MIR) family of E3 ligases affect antigen presentation by regulating lysosomal degradation of MHC class I antigens [ 76 ]. Multiple E3 ubiquitin ligase genes of the TRIM family are located in the MHC Class I region of chromosome 6 [ 77 ]. This includes TRIM27 , a gene included in the heatmap of differentially expressed E3 ligases in EPN ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The network analysis of Figure 6 illustrates the interaction of other E3 ligases on TRIM27 expression. The expression is related to inflammatory disesases and viral infections [ 77 ]. While some TRIM proteins have been associated with cancer [ 78 ], we could find no previous reports relating TRIM27 to EPN tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%